2016
DOI: 10.1002/elan.201600249
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Gold Electrodes with Tuneable Pore Sizes for Bioelectrochemical Applications

Abstract: Nanoporous gold (NPG) fabricated by sputtering is a material of versatile morphology with pores whose size can be tailored to accommodate enzymes. The process of pore formation and the size of the pores in NPG are influenced by the composition of Au and Ag in the alloy used to prepare the electrodes together with the temperature and time period of the dealloying process. On increasing the time from 1 to 60 min and the temperature from 0.5 °C to 60.5 °C in concentrated HNO3, significant increases in the average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 39 publications
3
46
0
Order By: Relevance
“…Note also that coupling of BOx through diazonium improved the stability of the electrodes substantially. In a previous report, we demonstrated that physically adsorbed BOx on NPG only showed catalytic activity for 4 h . In addition to the higher electrochemically active surface area, NPG electrodes clearly provide a more stable environment for the immobilized BOx enzyme.…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…Note also that coupling of BOx through diazonium improved the stability of the electrodes substantially. In a previous report, we demonstrated that physically adsorbed BOx on NPG only showed catalytic activity for 4 h . In addition to the higher electrochemically active surface area, NPG electrodes clearly provide a more stable environment for the immobilized BOx enzyme.…”
Section: Resultsmentioning
confidence: 71%
“…The structure and morphology of a metal surface produced by chemical etching of a bimetallic alloy can vary substantially depending on the etching conditions . NPG electrodes with a wide range of pore and crack sizes and substrate thicknesses (Table ) were utilized to evaluate the effects on current density and stability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations